Why packing adjustment cannot stop leakage: Case study of a ball valve failing to seal after packing adjustment during fugitive emission as per ISO 15848–1. (December 2021) - Sotoodeh, Karan
Highlights: Fugitive emission prevention in valves using ISO 15, 848 standard. Prevention of valve stem leakage. Understanding key factors lead to leakage from valve stem. Abstract: Valves are the main cause of fugitive emission in industrial plants, and leakage from valves occurs primarily from the stem. In this study, a 1″ ball valve in 10 bar of pressure was subjected to a fugitive emission test as per the ISO 15848–1 standard. This was the only valve required to be qualified for fugitive emission. The valve failed to provide the required sealing after 100 mechanical cycles, and excessive leakage occurred from the stem sealing. Consequently, the valve stem packing was tightened and the test was repeated. However, the leakage from the valve increased even after tightening the stem sealing through the gland. The valve was disassembled and the cause of the failure was identified as a deposit of graphite packing on the stem due to the roughness of the stem surface. After brainstorming with the valve manufacturer, the seven key causes of valve stem sealing failure during fugitive emission testing were identified, and the probability of each cause of failure was found. The question that remained was whether packing adjustment could reduce the probability of each kind of failure. We found that stem packing adjustment could mitigate three out of the seven factors that could cause valve stem leakage during the test. It was concluded that adjusting the gland could reduce the failure rates of stem emission 23.5% in the best and just 3% in the worst-case scenario.